Correlation analysis of ductus venosus velocity indices and fetal cardiac function. (3rd April 2014) - Sanapo, L.; Turan, O. M.; Turan, S.; Ton, J.; Atlas, M.; Baschat, A. A.
ABSTRACT Objective To examine the relationships between the ductus venosus (DV) pulsatility index for veins (PIV), individual DV velocity ratios and diastolic and global myocardial cardiac function. Methods Doppler measurements of the DV, atrioventricular (AV) valves and ventricular in‐ and outflow were analyzed. The DV‐PIV and velocity ratios for individual phases (systole (S), end‐systolic relaxation (v), early diastole (D), atrial systole (a), and S/v, S/D, S/a, v/D, v/a and D/a ratios) were calculated. The ratio of early and late diastolic peak velocities across AV valves was calculated (E/A ratio). Left modified myocardial performance index (MPI) was calculated from time intervals between valve clicks defining isovolumetric contraction/relaxation and ejection times. All values were transformed to Z‐scores. The distributions of DV velocity ratios and DV‐PIV were correlated with cardiac Doppler parameters. Results A total of 1163 examinations from 213 fetuses, most of which were at risk for cardiac dysfunction, were included in the study. In 742 the PIV was normal and in 421 PIV was elevated > 2 SD above the normal mean. The DV‐PIV correlated with velocity ratios (P < 0.0001) but not with E/A ratios and the MPI. S/v and v/D ratios were related to tricuspid and mitral E/A ratios and left ventricular MPI. The S/D ratio was only related to both E/A ratios. There was no relationship between a‐wave‐related velocity ratios and cardiac function. Conclusions Velocity ratios of the DV show relationships with cardiac function that are not reflected by the PIV alone. In cases of suspected fetal cardiac dysfunction based on elevated DV‐PIV, analysis of velocity ratios or direct cardiac evaluation is suggested to determine the underlying pathophysiology. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.